Short-range connections in the developmental connectome during typical and atypical brain maturation. (December 2017) - Ouyang, Minhui; Kang, Huiying; Detre, John A.; Roberts, Timothy P.L.; Huang, Hao
Highlights: Short-range connectivity plays a key role in information transfer in human brain. It contributes to segregation and integration of developmental connectome. Its maturation is spatiotemporally unique and heterogeneous in typical development. Its maturation follows the sequence from primary to higher-order brain regions. Alterations of short-range connections are associated with autism and schizophrenia. Abstract: The human brain is remarkably complex with connectivity constituting its basic organizing principle. Although long-range connectivity has been focused on in most research, short-range connectivity is characterized by unique and spatiotemporally heterogeneous dynamics from infancy to adulthood. Alterations in the maturational dynamics of short-range connectivity has been associated with neuropsychiatric disorders, such as autism and schizophrenia. Recent advances in neuroimaging techniques, especially diffusion magnetic resonance imaging (dMRI), resting-state functional MRI (rs-fMRI), electroencephalography (EEG) and magnetoencephalography (MEG), have made quantification of short-range connectivity possible in pediatric populations. This review summarizes findings on the development of short-range functional and structural connections at the macroscale. These findings suggest an inverted U-shaped pattern of maturation from primary to higher-order brain regions, and possible "hyper-" and "hypo-" short-range connections in autism and schizophrenia, respectively. The precisely balanced short- and long-range connections contribute to the integration and segregation of the connectome during development. The mechanistic relationship among short-range connectivity maturation, the developmental connectome and emerging brain functions needs further investigation, including the refinement of methodological approaches.